Experimental study on displacement monitoring of instable highway slope based on MEMS sensors - Wu, Di; Liang, Taiming; Yang, Yanxin; Pei, Qingpeng; Yi, Yang; Wu, Jianjian; Li, Dan (Frontiers in Earth Science, 2025)
IntroductionThe monitoring of soil displacement during highway slope instability currently faces challenges such as poor stability, low accuracy, and high costs. In this study, a Micro-Electro-Mechanical System (MEMS) sensor is proposed for measuring internal soil displacement during slope movement. A method for converting MEMS-based acceleration signals into displacement data is also developed.MethodsTo evaluate the applicability of MEMS technology for deep displacement monitoring, an indoor model test was conducted using a highway slope composed of gravelly soil from Jiangxi Province as a case study. Three slope models with varying gravel contents (20%, 40%, and 60%) were designed to simulate displacement caused by slope instability. Displacement data obtained from the MEMS sensors were analyzed and compared with Particle Image Velocimetry (PIV) data.Results and DiscussionThe results showed that the average relative errors of vertical displacement for the MEMS sensor compared to PIV at three measurement points in the sliding area were 5.79%, 5.54%, and 5.89% for slopes with 20%, 40%, and 60% gravel content, respectively. Similarly, the average relative errors of horizontal displacement were 6.11%, 5.21%, and 4.73%. These findings indicate that the trends in soil movement within the sliding area correspond to changes in gravel content. Furthermore, the relatively small average relative errors of the MEMS sensor demonstrate its feasibility and potential for deep soil displacement monitoring in slope stability studies.